Impairment of muscular endothelial cell regeneration in dermatomyositis - Lemmer, D.; Schmidt, J.; Kummer, K.; Lemmer, B.; Wrede, A.; Seitz, C.; Balcarek, P.; Schwarze, K.; Müller, G. A.; Patschan, D.; Patschan, S. (Frontiers in Neurology, 2022)
Background and aim Inflammatory myopathies is a group of heterogeneous subsets in terms of etiology, (immuno)pathology, and clinical findings. Endothelial cell injury, as it occurs in DM is a common fea-ture of numerous inflammatory and non-inflammatory vascular diseases. Vascular regeneration is mediated by both, local and blood-derived mechanisms such as the mobilization and activation of so-called proangiogenic cells (PACs) or early Endothelial Progenitor cells (eEPCs). The current study aimed to evaluate parameters of eEPC integrity in dermatomyositis (DM), com-pared to necrotitzing myopathy (NM) and to non-myopathic controls. Methods Blood samples from DM and NM patients were compared to non-myopathic controls and analyzed for the following parameters: circulating CD133+/VEGFR-2+ cells, number of Colony-Forming Unit Endothelial Cells (CFU-ECs), concentrations of Angiopoietin 1, Vascular Endothelial Growth Factor (VEGF) and CXCL-16. Muscle biopsies from DM and NM subjects underwent immunofluorescence analysis for CXCR6, Nestin, and CD31 (PECAM-1). Finally, myotubes, derived from healthy donors were stimulated with serum samples from DM and NM patients, subsequently followed by RT-PCR for the following candidates: IL-1, IL-6, Nestin, and CD31. Results Seventeen (17) DM patients, 7 NM patients and 40 non-myopathic controls were included. CD133+/VEGFR-2+ cells did not differ between the groups. Both, DM and NM patients showed lower CFU-ECs than controls. In DM, intramuscular CD31 abundances were significantly reduced, which indicated vascular rarefaction. Muscular CXCR6 was elevated in both diseases. Circulating CXCL-16 was higher in DM and NM in contrast, compared to controls. Serum from patients with DM but not NM induced a profound upregulation of mRNS expression of CD31 and IL-6 in cultured myotubes. Conclusions Our study demonstrates the loss of intramuscular microvessels in DM, accompanied by endo-thelial activation in DM and NM. Vascular regeneration was impaired in DM and NM. The findings suggest a role for inflammation-associated vascular damage in the pathogenesis of DM.